Pengembangan Modul Ajar Berdiferensiasi Berbasis Kurikulum Merdeka dengan Pendekatan Pendidikan Matematika Realistik - Datu, Pratiwi Ardin; Pomalato, Sarson W. Dj; Panigoro, Hasan S. (Department of Mathematics, Universitas Negeri Gorontalo, 2024)
This research is development research and aims to produce a teaching device in the form of an emancipated curriculum-based module with a realistic mathematics education approach that is valid, practical, and effective. This research employs the 4- D development model conducted on the seventh grade students at SMPN 1 Kwandang, North Gorontalo Regency, in the first semester of the academic year 2022/2023. The results indicate that the quality of the developed product meets the criteria of validity, practicality, and effectiveness. This is proven by the validation results for the teaching module, where the average score given by the validators is 96.8%, indicating that it is categorized as highly valid. The analysis of the practicality aspect during the small-scale trial yielded scores ranging from 81% to 100%, meeting the criteria of being highly practical. The large-scale trial also indicates an average score of 100% with a highly practical rating. The effectiveness aspect was analyzed based on the students learning test results, which had an average score of 92.0%. In conclusion, with a realistic mathematics education approach, the emancipated curriculum-based mathematics teaching module is valid, practical, and effective for algebra material in seventh grade at SMPN 1 Kwandang.